The strategies to serve and conserve Moroccan durum wheat genetic diversity before it is lost - Ramdani A.; Ouabbou H.; Nsarellah N.; Lhaloui S.; Abbad-Andaloussi F.; Nachit M.M.; Bhavani S.; Nazari K.; Wanyera R.; Ferrahi M.; Haddoury J.; Udupa S.M. (Proceedings of the International Symposium on Genetics and breeding of durum wheat, 2014)
Morocco is considered as a center of diversity of many species, including Triticum spp. This diversity is under the verge of extinction and hence urgent actions are needed to conserve it. Many actions are undertaken to reach that goal. Collecting missions were undertaken across Morocco and accessions are preserved at Gene Bank of Morocco. To widen this collection, recently two collecting missions were undertaken. One covered the Atlas Mountains, Ziz and Daraa valleys and carried out during 2009-10 cropping season, and the other covered the northern part of Morocco and carried out during 2010-11. The number of accessions collected were 16 in the South and 6 in the North. To assess the variation present in the Moroccan material, accessions from different provinces were tested along with improved cultivars were tested at different experimental station during 2009-11. The results indicated that the most prevalent diseases were yellow rust and to some extent leaf rust. Some of the old accessions are good sources of resistance to these diseases. To promote on-farm conservation of landraces, on-farm field experiments using the same sub-core collection were carried out at different places. The result of these trials revealed that almost all improved cultivars were selected both by farmers and scientists along with some landraces. The magnitude of the positive correlation between agronomic scores attributed by farmers and scientists shed light on the importance to involve farmers in selection. The main traits of selection by the latter are grain yield, biomass, grain size and color, and earliness.
International Symposium : Genetics and Breeding of Durum Wheat, 2013/05/27-30, Rome (Italy)